2019
DOI: 10.18632/aging.101993
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide phosphoribosyltransferase postpones rat bone marrow mesenchymal stem cell senescence by mediating NAD+–Sirt1 signaling

Abstract: In vitro replicative senescence affects MSC characteristics and functionality, thus severely restricting their application in regenerative medicine and MSC-based therapies. Previously, we found that MSC natural senescence is accompanied by altered intracellular nicotinamide adenine dinucleotide (NAD + ) metabolism, in which Nampt plays a key role. However, whether Nampt influences MSC replicative senescence is still unclear. Our study showed that Nampt expression is down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 63 publications
(61 reference statements)
8
39
0
Order By: Relevance
“…The previous studies indicated that cell proliferation slowed down, the PDT increased, osteogenic and adipogenic differentiation potentials diminished, and cell cycle arrested in senescent MSCs ( Ma et al, 2017 ; Pi et al, 2019 ), consistent with our present results. Importantly, MSC senescence has contributed to tissue, organ, and organism aging and age-related diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The previous studies indicated that cell proliferation slowed down, the PDT increased, osteogenic and adipogenic differentiation potentials diminished, and cell cycle arrested in senescent MSCs ( Ma et al, 2017 ; Pi et al, 2019 ), consistent with our present results. Importantly, MSC senescence has contributed to tissue, organ, and organism aging and age-related diseases.…”
Section: Discussionsupporting
confidence: 93%
“…The cells were transduced with lentiviral particles encoding rat Sirt3 or control vector as previously described ( Pi et al, 2019 ). Briefly, cells were plated at 1.5 × 10 5 /well in six-well plate and incubated at 37°C for 18 h, and then, cells were transduced with lentivirus-expressing Sirt3 in the presence of 4 μg/ml polybrene (Genechem Co. Ltd., China) for 12 h. Sirt3 over-expressed MSCs were used in subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, visfatin caused an increase in γH2AX foci in hDPCs, whereas FK866 attenuated visfatin-induced cellular senescence, which was accompanied by a decrease in γH2AX foci and the downregulation of p21. These results suggest that visfatin signaling induces dental pulp cell senescence, which is consistent with the results on human endothelial cells [30] but inconsistent with the inhibitory effects of visfatin on the senescence of other cell types [29,45,46]. The reason for this discrepancy is unclear but may result from cell-context-dependent visfatin signaling.…”
Section: Discussionsupporting
confidence: 61%
“…While visfatin is highly expressed in cardiovascular and inflammatory diseases, as well as in various cancers [16], its role in tissue aging and cellular senescence is controversial. Visfatin has been shown to delay cellular senescence via NAD(+)-Sirt1 signaling in mesenchymal stem cells, endothelial progenitor cells, aortic smooth muscle cells, and fibroblasts [29,45,46]. In addition, inhibition of visfatin with FK866 has been shown to promote cellular senescence in retinal pigment epithelium [28].…”
Section: Discussionmentioning
confidence: 99%
“…174,175 Similarly, with cancer, autoimmune and metabolic syndromes, there is biochemical evidence of loss of nicotinamide homeostasis, whether dietary from increased consumption or excessive catabolism, or implied from benefits of measurement and intervention. 153,176-203…”
Section: Diseases Of Protons Proles and Patriciansmentioning
confidence: 99%